Long term outcomes of saphaneous vein graft intervention in elderly patients with prior coronary artery bypass graft - Wang, Ji-Hong; Liu, Wei; Du, Xin; Ma, Chang-Sheng; Wu, Xue-Si (Journal of geriatric cardiology : JGC, 2014)
Objectives To investigate the procedure characteristics and long term follow-up ofpercutaneous coronary intervention （PCI） for sa phaneous vein graft （SVG） lesions in the elderly patients. Methods From December 2005 to December 201 l, 84 graft lesions were treated percumneously. Seventeen were located at proximal anastomosis, 48 were located at SVG body, 19 were located at distal anastomosis. Pri mary endpoint was defined as major adverse cardiovascular events （MACE, composite of cardiac death, target vessel revascularization, acute myocardial infarction）. Results The graft age was 6.7 i 4.0 years. Most anastomosis lesions （80.0%） presented within one year post coro-nary artery bypass grafting （CABG）. Proximal anastomosis lesion had the lowest successful rate for PCI compared with graft body and distal anastomosis lesions （70.6% vs. 91.7%, 79.0%, P 〈 0.05）. The distal embolic protection device was used in 19.1% of patients, most frequently used in body graft PCI （29.2%, P 〈 0.01）. The diameter of the stent was smallest in distal anastomosis group （2.9 ±0.4 mm, P 〈 0.05）. The highest post dilatation pressure was required in the proximal anastomosis （17.8 ± 2.7 atm, P 〈 0.05）. The patients were followed up for 24.3 ±16.9 months. MACE occurred in 18.57% of patients. Incidence of MACE was highest among proximal anastomosis PCI （47.1% vs. body graft PCI 16.7%, distal anastomosis PCI 21.1%; P 〈 0.05）. Old myocardial infarction was the predictive factor for the poor clinical outcomes （P〈 0.04）. Conclusions PCI of SVG lesions is feasible with lower success rate. PCI of ostial graft anastomosis lesions had the lowest procedure success rate and highest MACE rate compared with graft body and distal anastomosis lesions. Old myocardial infarction was a predictive factor of poor outcomes.